The Role of Bridging Water and Hydrogen Bonding as Key Determinants of Noncovalent Protein–Carbohydrate Recognition. (21st November 2018) - Ruvinsky, Anatoly M.; Aloni, Ishita; Cappel, Daniel; Higgs, Chris; Marshall, Kyle; Rotkiewicz, Piotr; Repasky, Matt; Feher, Victoria A.; Feyfant, Eric; Hessler, Gerhard; Matter, Hans
Abstract: Mechanisms of protein–carbohydrate recognition attract a lot of interest due to their roles in various cellular processes and metabolism disorders. We have performed a large‐scale analysis of protein structures solved in complex with glucose, galactose and their substituted analogues. We found that, on average, sugar molecules establish five hydrogen bonds (HBs) in the binding site, including one to three HBs with bridging water molecules. The free energy contribution of bridging and direct HBs was estimated using the free energy perturbation (FEP+) methodology for mono‐ and disaccharides that bind tol ‐ABP, ttGBP, TrmB, hGalectin‐1 and hGalectin‐3. We show that removing hydroxy groups that are engaged in direct HBs with the charged groups of Asp, Arg and Glu residues, protein backbone amide or buried water dramatically decreases binding affinity. In contrast, all solvent‐exposed hydroxy groups and hydroxy groups engaged in HBs with the solvent‐exposed bridging water molecules contribute weakly to binding affinity and so can be replaced to optimize ligand potency. Finally, we rationalize an effect of binding site water replacement on the binding affinity tol ‐ABP. Abstract : Key OHs for ligand potency : This work combines a PLDB‐wide structure analysis with binding affinity calculations by FEP+ and WaterMap to explore the role of water molecules and hydrogen bonding in molecular recognition of mono‐ and disaccharides. We analyze distributions of hydrogen bonds and suggest an approach to identify hydroxy groups in sugars that are important for binding affinity. We show that, typically, such hydroxy groups are engaged in direct hydrogen bonds with the charged groups of Asp, Arg, and Glu residues, protein backbone amide or buried water molecules.